2004
DOI: 10.1152/ajplung.00014.2004
|View full text |Cite
|
Sign up to set email alerts
|

Fractalkine/CX3CL1 production by human airway smooth muscle cells: induction by IFN-γ and TNF-α and regulation by TGF-β and corticosteroids

Abstract: mokine synthesis by airway smooth muscle cells (ASMC) may be an important process underlying inflammatory cell recruitment in airway inflammatory diseases such as asthma and chronic obstructive pulmonary disease (COPD). Fractalkine (FKN) is a recently described CX 3C chemokine that has dual functions, serving as both a cell adhesion molecule and a chemoattractant for monocytes and T cells, expressing its unique receptor, CX3CR1. We investigated FKN expression by human ASMC in response to the proinflammatory cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 60 publications
4
65
0
Order By: Relevance
“…Although TGF-␤ may play an important role in remodeling, it has antiinflammatory properties. For example, TGF-␤ inhibits fractalkine (CX 3 CL) release induced by TNF-␣ and IFN-␥ from airway smooth muscle cells (83).…”
Section: Tgf-␤mentioning
confidence: 99%
“…Although TGF-␤ may play an important role in remodeling, it has antiinflammatory properties. For example, TGF-␤ inhibits fractalkine (CX 3 CL) release induced by TNF-␣ and IFN-␥ from airway smooth muscle cells (83).…”
Section: Tgf-␤mentioning
confidence: 99%
“…F ractalkine (FKN), 4 or CX3CL1, is a CX3C chemokine expressed as a membrane-bound form (1) by several cell types, including vascular smooth muscle cells (2,3). Recently, it has been shown that human airway smooth muscle cells (HASMC), also can produce FKN upon stimulation by proinflammatory cytokines (4).…”
mentioning
confidence: 99%
“…Recently, it has been shown that human airway smooth muscle cells (HASMC), also can produce FKN upon stimulation by proinflammatory cytokines (4). FKN interacts with its unique receptor CX3CR1 (5) on monocytes, NK cells, and T cells and mediates both adhesion and migration of leukocytes.…”
mentioning
confidence: 99%
“…However, two coding SNPs (T280M and V249I) have been shown to affect risk to other diseases involving immune and inflammatory diseases. [19][20][21][22][23] Based on our observations that the CX3CR1 gene is less expressed in bronchial biopsies of asthmatic subjects, 6 its biological importance in the recruitment of leukocytes in the inflammatory sites 8,9,12 and its potential role in allergic asthma, 17,18 we hypothesize that CX3CR1 is a candidate gene in asthma pathogenesis. The aims of this study were to carry out an association study and a haplotypic analysis with selected SNPs in CX3CR1 gene in a founder effect familial asthmatic sample from northeastern Quebec.…”
Section: Introductionmentioning
confidence: 96%
“…9 A role for CX3CR1-FKN-mediated inflammation has been suggested in various inflammatory diseases including vascular injury, 15 atopic dermatitis 16 and allergic airway diseases. 17,18 To our knowledge, no genetic association study has been reported between CX3CR1 and asthma. However, two coding SNPs (T280M and V249I) have been shown to affect risk to other diseases involving immune and inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%